Determining the Bordetella LPS structural features that influence TLR4 downstream signaling - Manivannan, Kiruthika; Fathy Mohamed, Yasmine; Fernandez, Rachel C. (Frontiers in Microbiology, 2025)
Upon recognizing bacterial lipopolysaccharide (LPS), human TLR4 initiates two distinct signaling pathways: the MyD88 pathway from the cell surface or the TRIF pathway following endocytosis. While the first is associated with strong pro-inflammatory responses, the latter is linked to dendritic cell maturation and T cell priming. Changes in LPS structure can influence the activation of either or both pathways. This study investigates the influence of specific structural features of Bordetella LPS on these pathways: the O antigen, the number of acyl chains in lipid A and the glucosamine modification of the phosphates of the lipid A diglucosamine backbone. Systematically engineered Bordetella LPS differing in one or more of these features were studied by quantifying NFκB and IRF3 activation—indicators of MyD88 and TRIF pathway activation, respectively. The findings reveal that the glucosamine modification of lipid A plays a dominant role in TLR4-mediated signaling, overriding the influence of the O antigen and lipid A acylation. The absence of glucosamine modification significantly reduced the activation of both MyD88 and TRIF pathways, underscoring its importance in promoting TLR4 dimerization. Furthermore, under-acylation of LPS (with 4 or 5 acyl chains) partially reduced NFκB activation, while completely abrogating TRIF pathway activation. In contrast, hexa-and hepta-acylated LPS equally and robustly activated both pathways. Lastly, the Bordetella O antigen selectively biased signaling towards the TRIF pathway without affecting the MyD88 pathway. This study provides valuable insights into how specific LPS structural modifications can be leveraged to tailor TLR4-mediated signaling.